Putting the "We" Into Well‐being: Using Collectivism‐Themed Measures of Well‐Being Attenuates Well‐being's Association With Individualism. Issue 3 (29th April 2019) - Krys, Kuba; Zelenski, John M.; Capaldi, Colin A.; Park, Joonha; van Tilburg, Wijnand; van Osch, Yvette; Haas, Brian W.; Bond, Michael H.; Dominguez‐Espinoza, Alejandra; Xing, Cai; Igbokwe, David O.; Kwiatkowska, Anna; et al.
Abstract : Studies repeatedly have documented that societal well‐being is associated with individualism. Most of these studies, however, have conceptualized/measured well‐being as individual life satisfaction—a type of well‐being that originates in Western research traditions. Drawing from the latest research on interdependent happiness and on family well‐being, we posit that people across cultures pursue different types of well‐being, and test whether more collectivism‐themed types of well‐being that originate in Confucian traditions also are associated with individualism. Based on data collected from 2, 036 participants across 12 countries, we find support for the association between individual life satisfaction and individualism at the societal level, but show that well‐being's association with individualism is attenuated when some collectivism‐themed measures of well‐being are considered. Our article advances knowledge on the flourishing of societies by suggesting that individualism may not always be strongly linked with societal well‐being. Implications for public policies are signaled.